Impact of Patients’ Motivation and Scheme of Positive and Negative Symptoms among Patients with Psychotic Disorders - Rashid, Saima; jillani, Uzma; Khanum, Sanober; Shahzadi, Mafia; Unbrin, Aqila (Pakistan Journal of Humanities and Social Sciences, 2024)
Positive motivations toward treatment are an important factor that plays a significant role in the treatment outcomes and patients' recovery process. The present study investigates the impact of patients’ motivation toward treatment and its impact on patients positive, negative, and general psychopathological symptoms among patients with psychosis. A total of 200 participants diagnosed with psychotic disorders were approached from different hospitals and clinics in Faisalabad and Karachi. 11 out of 200 participants were excluded due to comorbid conditions and unclarity in diagnostic symptoms. 189 participants met the inclusion and exclusion criteria of the study. Both male 112(59.26%) and females 77(40.74%). patients were included in this study. Participants were taken from all socioeconomic statuses. Participants’ age range was between 20 to 45 years with M±SD=34.53±2.57. Findings show that patients a significant difference was estimated in positive, negative and general psychopathological symptoms between patients with low motivation and high motivation. Furthermore, results indicate that a significant difference was estimated in positive, negative and general psychopathological symptoms between patients with schizophrenia disorder and other psychotic disorders among patients with psychotic disorders. It is concluded that low motivation toward treatment is suspected a lower chance of engagement in treatment as compared to those who have high motivation. Patients with schizophrenia disorder perceived relevantly high symptom severity on positive, negative, and general psychopathological symptoms as compared to other psychotic disorders.